Optimization of damped outrigger systems subject to stochastic excitation - Fang, Chuangjie; Spencer, Billie F.; Xu, Jiaqi; Tan, Ping; Zhou, Fulin (Engineering structures, 2019)
•Stochastic optimization procedure is proposed for structure design.•The proposed optimization procedure is applied to damped outrigger system.•Pareto optimal front is used to examine the tradeoffs between conflicting objectives.•Harmful interstory drift and Timoshenko beam model are used to better describe structural interstory drift. High-rise buildings have attracted much attention with the continuing growth of world population and increasing urbanization. As buildings become taller, suppressing excessive vibration due to lateral excitation becomes more challenging. One of the promising solutions that has been proposed is the damped outrigger system, where dampers are vertically installed between outriggers attached to the core and perimeter columns, leading to a significant increment of structural damping. To gain insight into the design of damped outrigger systems subject to seismic excitation, a stochastic optimization procedure is proposed. The seismic excitation is modeled as a filtered white noise, following the Kanai-Tajimi spectrum. To better represent the interstory drift, the core of the building is modeled using a Timoshenko beam, and a Kelvin model of the damper is considered. The equations of motion of the structure-damper-excitation system are combined into an augmented state space representation. The variance of the responses of the structure are calculated via solution of the Lyapunov equation. A genetic algorithm is used to determine the damper placement and associated parameters so as to minimize objective function, which is in terms of the structural responses. A Pareto optimal front is used to examine the tradeoffs with respect to minimizing interstory drift, floor accelerations, base shear, and base overturning moment. The results demonstrate the efficacy of the proposed approach, reveal the range of application for such damped outrigger systems, and provide insight into the system design in the presence of seismic excitation.